A case study of two Muslim Non-Governmental Organizations(NGOs) on Islamic da`wah in Nigeria (IR) - Sonfada Usman (2015)
The propagation of Islam (da`wah) by different Muslim organizations in Nigeria and across the globe in helping humanity especially in the area of education is on the rise. The main objective of this study is to explore the contributions of Jamaatu Nasir Islam (JNI) and Nasirul-Lahi Fatih Society of Nigeria (NASFAT) in Islamic da`wah in Niger State, Nigeria. This study employed a qualitative approach. The instrument used in this study includes interviews, observation and documents analysis. The respondents are eleven executive members of the two organizations. The qualitative design was utilized and data was compiled from transcriptions of recorded interviews and observations. The narrative and qualitative software known as Nvivo 10 were used in managing and analysing the data. The research findings show the contributions of the two Muslim organizations through da`wah in the state which have made significant contributions towards the spread of Islam most especially in the field of education, having more converts from other religions to the fold of Islam. As a result, both organizations do not show much differences in their approach toda`wah. The research indicates that Jamaatu Nasir Islam portray a more quality da`wah activities than NASFAT. In conclusion, the outcomes of the research showed that both Jamaatu Nasir Islam and NASFAT were able to touch lives of many people in the state through da`wah programs. The results of this study might be useful for future study on Muslim organizations in Nigeria and also of help to Islamic Supreme Council of Nigeria (ISCN), for easy assessment of dawah programs by these two Muslim organizations in the state.